Irradiation induced reactions in carbon nanomaterials in transmission electron microscopy - Skowron, Stephen T. (2016)
Aberration corrected transmission electron microscopy is a powerful tool for the structural characterisation of materials at the atomic scale, but the passage of high velocity electrons through the material can often induce structural changes via the transfer of large amounts of energy from the beam. The work in this thesis theoretically considers the nature of this transfer of energy and its impact upon the material being studied. The computational modelling of molecular species encapsulated inside carbon nanotubes and their response to electron irradiation is compared to results from TEM experiments, and used to explain the experimental observations. The high rate of destruction of C-H bonds under the beam is quantified, and its implications for TEM studies of organic materials considered. An effective solution for mitigating this rate of destruction is found, applied to a model system, and then confirmed experimentally. Using the considerations of stability under the beam, two experimentally witnessed reactions are investigated in detail, and careful comparison to intermediate structures observed in TEM allows full reaction mechanisms to be proposed. The dynamic motion of atomic defects in irradiated graphene is considered with the aid of a large library of experimental TEM images. A novel defect structure is observed, and is seen to undergo structural rearrangements on a quicker time-scale than accessible to TEM imaging. This species enables the very quick migration of defect structures across the graphene lattice, and is attributed to a trivacancy structure. The rates of beam induced reactions are considered in the framework of chemical kinetics, and a method for extracting kinetic parameters of a reaction from the statistics of a large number of TEM observations of it occurring is developed. This is used to obtain the first cross-sections for the formation and healing of the irradiation induced Stone-Wales bond rotation, and the first experimental activation energy for its healing. The latter agrees well with a theoretically predicted mechanism of catalysis, while the former demonstrates that the widely assumed process of direct knock-on damage cannot be responsible for the beam induced reaction. An alternative mechanism is proposed, resulting from the electronic excitation of the defect.